The Effect of Capital Flows Composition on Output Volatility - Federico, Pablo; Vegh, Carlos A.; Vuletin, Guillermo (World Bank, Washington, DC, 2013)
A large literature has argued that different types of capital flows have different consequences for macroeconomic stability. By distinguishing between foreign direct investment and portfolio and other investments, this paper studies the effects of the composition of capital inflows on output volatility. The paper develops a simple empirical model which, under certain conditions that hold in the data, yields three key testable implications. First, output volatility should depend positively on the volatilities of both foreign direct investment and portfolio and other inflows. Second, output volatility should be an increasing function of the correlation between both kinds of inflows. Third, output volatility should be a decreasing function of the share of foreign direct investment in total capital inflows, for low values of that share. The data provide strong support for all three implications, even after controlling for other factors that may influence output volatility, and after dealing with potential endogeneity problems. These findings call attention to the importance of taking into account the synchronization and composition of capital flows for output stabilization purposes, as opposed to just focusing on the volatility of each component of capital flows.